Fitness, insulin sensitivity, and frontal lobe integrity in adults with overweight and obesity. Issue 6 (28th April 2016) - Castro, Mary Grace; Venutolo, Christopher; Yau, Po Lai; Convit, Antonio
Abstract : Objective: To formally test whether insulin sensitivity mediates the relationship between fitness and brain integrity. Methods: Eighty‐four middle‐aged participants without diabetes received a 6‐min walk test from which maximal oxygen uptake (VO2 max) was derived, a structural magnetic resonance scan, and a medical evaluation including fasting glucose and insulin levels. Results: This study showed significant associations between fitness, abdominal obesity, and insulin sensitivity and anterior cingulate cortex (ACC) volume as well as between ACC thickness and quantitative insulin‐sensitivity check index (QUICKI). The relationship between ACC volume and VO2 max was completely mediated through QUICKI. Further, this strong association was confirmed by a single and very significant cluster on the ACC linking gray matter volume and QUICKI in a voxel‐based morphometry analysis. Conclusions: As expected, increased abdominal obesity was associated with reductions in fitness, ACC volumes, and insulin sensitivity. Importantly, this study demonstrated a significant mediation of the relationship between VO2 max and ACC volume by QUICKI. This suggests that the links between impaired insulin sensitivity and brain abnormalities in adults carrying excess weight could be alleviated through increased physical activity and fitness.